Audiovisual speech perception in children with autism spectrum disorders: Evidence from visual phonemic restoration. - Irwin, Julia; Avery, Trey; Kleinman, Daniel; Landi, Nicole (Journal of autism and developmental disorders, 2021)
Children with autism spectrum disorders have been reported to be less influenced by a speaker’s face during speech perception than those with typically development. To more closely examine these reported differences, a novel visual phonemic restoration paradigm was used to assess neural signatures (event-related potentials [ERPs]) of audiovisual processing in typically developing children and in children with autism spectrum disorder. Video of a speaker saying the syllable /ba/ was paired with (1) a synthesized /ba/ or (2) a synthesized syllable derived from /ba/ in which auditory cues for the consonant were substantially weakened, thereby sounding more like /a/. The auditory stimuli are easily discriminable; however, in the context of a visual /ba/, the auditory /a/ is typically perceived as /ba/, producing a visual phonemic restoration. Only children with ASD showed a large /ba/-/a/ discrimination response in the presence of a speaker producing /ba/, suggesting reduced influence of visual speech. © 2021, The Author(s), under exclusive licence to Springer Science+Business Media, LLC part of Springer Nature.
4 citations (Crossref) [2023-10-31] Type: Article tex.citation: https://api.elsevier.com/content/abstract/scopus_id/85101748846
Keywords: Auditory Perception; Autism Spectrum Disorder; Child; Cues; Evoked Potentials; Humans; Speech; Speech Perception; Visual Perception; association; autism; child; dept.psy; evoked response; hearing; human; peer-reviewed; speech; speech perception; vision

Neural and Behavioral Differences in Speech Perception for Children With Autism Spectrum Disorders Within an Audiovisual Context - Irwin, Julia; Harwood, Vanessa; Kleinman, Daniel; Baron, Alisa; Avery, Trey; Turcios, Jacqueline; Landi, Nicole (Journal of Speech, Language, and Hearing Research, 2023)
Purpose: Reduced use of visible articulatory information on a speaker's face has been implicated as a possible contributor to language deficits in autism spectrum disorders (ASD). We employ an audiovisual (AV) phonemic restoration paradigm to measure behavioral performance (button press) and event-related potentials (ERPs) of visual speech perception in children with ASD and their neurotypical peers to assess potential neural substrates that contribute to group differences. Method: Two sets of speech stimuli, /ba/–“/a/” (“/a/” was created from the /ba/ token by a reducing the initial consonant) and /ba/–/pa/, were presented within an auditory oddball paradigm to children aged 6–13 years with ASD (n = 17) and typical development (TD; n = 33) within two conditions. The AV condition contained a fully visible speaking face; the pixelated (PX) condition included a face, but the mouth and jaw were PX, removing all articulatory information. When articulatory features were present for the /ba/–“/a/” contrast, it was expected that the influence of the visual articulators would facilitate a phonemic restoration effect in which “/a/” would be perceived as /ba/. ERPs were recorded during the experiment while children were required to press a button for the deviant sound for both sets of speech contrasts within both conditions. Results: Button press data revealed that TD children were more accurate in discriminating between /ba/–“/a/” and /ba/–/pa/ contrasts in the PX condition relative to the ASD group. ERPs in response to the /ba/–/pa/ contrast within both AV and PX conditions differed between children with ASD and TD children (earlier P300 responses for children with ASD). Conclusion: Children with ASD differ in the underlying neural mechanisms responsible for speech processing compared with TD peers within an AV context.
0 citations (Crossref) [2023-10-31]
Keywords: dept.psy; peer-reviewed